2022
DOI: 10.1007/s11433-022-2033-2
|View full text |Cite
|
Sign up to set email alerts
|

Peering into the Milky Way by FAST: III. Magnetic fields in the Galactic halo and farther spiral arms revealed by the Faraday effect of faint pulsars

Abstract: The Five-hundred-meter Aperture Spherical radio Telescope (FAST) is the most sensitive radio telescope for pulsar observations. We make polarimetric measurements of a large number of faint and distant pulsars using the FAST. We present the new measurements of Faraday rotation for 134 faint pulsars in the Galactic halo. Significant improvements are also made for some basic pulsar parameters for 15 of them. We analyse the newly determined rotation measures (RMs) for the Galactic magnetic fields by using these 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The degrees of linear, circular and absolute circular polarization and their uncertainties are listed in columns (10)-( 12) respectively. We obtain new RMs (i.e., RM = RM obs − RM ion ) for 402 pulsars as given in column (13), which have been employed to investigate the magnetic fields in the Galaxy by Xu et al (2022). The figure number for polarization profile, and the short notes as well as references for profile comparison are given in columns ( 14)-( 16) respectively.…”
Section: Fast Pulsar Polarization Profilesmentioning
confidence: 99%
“…The degrees of linear, circular and absolute circular polarization and their uncertainties are listed in columns (10)-( 12) respectively. We obtain new RMs (i.e., RM = RM obs − RM ion ) for 402 pulsars as given in column (13), which have been employed to investigate the magnetic fields in the Galaxy by Xu et al (2022). The figure number for polarization profile, and the short notes as well as references for profile comparison are given in columns ( 14)-( 16) respectively.…”
Section: Fast Pulsar Polarization Profilesmentioning
confidence: 99%
“…We obtain a sample of the RMs of 59,233 background radio sources, with the overall mean number density of 1.5 deg −2 (see Figure 1). For pulsars, except for the RMs collected from radio observations all over the world (Manchester et al 2005), we have also got our own pulsar RM data for faint pulsars (Xu et al 2022;Wang et al 2023), observed by using the Five-hundred-meter Aperture Spherical radio Telescope (FAST; Nan 2008). In total, we have the RMs of 634 pulsars at Galactic latitudes greater than 8°(see Figure 1).…”
Section: Faraday Rotation Measure Datamentioning
confidence: 99%
“…The remaining pulsars are too faint to be measured efficiently for RMs by other radio telescopes. We carried out the FAST polarization observations by two projects (PT2020_0164 and PT2021_0051) from 2020 October to 2021 November, and we determined new RM values for 134 faint halo pulsars (Xu et al 2022). The pulsar data density is improved in the left-sky part (i.e., the first and the second quadrants of our Galaxy).…”
Section: Faraday Rm Data Of Pulsarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Five-hundred-meter Aperture Spherical radio Telescope, FAST, has done this survey as part of the Galactic Plane Pulsar Snapshot (GPPS) Survey [2]. The primary goal is to find pulsars in the Galactic plane, 500 have been found already, but the survey has secondary applications to mapping the neutral atomic interstellar medium with the HI line [1], the ionized medium using recombination lines [3], and the magnetic field through measurement of Faraday rotation of pulsars [4]. This special edition includes papers describing results of all these projects; the background and significance of the HI data are considered in this News & Views piece.…”
mentioning
confidence: 99%